The other side of weight loss : a Lacanian autoethnography of weight-anxiety : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Organisation Studies at Massey University, Manawatu, New Zealand - Dickson, Andrew Gordon (Massey University, 2011)
This thesis critically re-thinks the organisation of the weight loss industry using a psychoanalytic framework derived from the work of Jacques Lacan, including his discourse theory. Further, I develop critical methodology by focusing on my own experiences and culture. I do this by gathering and analysing autoethnographic data. The main findings of this thesis occur in three broad topic areas. First I re-conceptualise the unconscious processes of the weight-loss subject and subsequently re-focus on the weight loss industry’s unconscious target: anxiety. Second I re-think the gender of the weightanxious subject, moving past biology and hegemony to think psychoanalytically about those subjects who identify as weight-anxious. Third I tackle the ethics of the wider weight loss industry, critically analysing its capitalistic focus and suggesting instead an ethics based on the desire of the weight-anxious subject. Finally I attempt to look at my thesis in reflection, by concluding in line with Lacan’s four discourses, finishing as the psychoanalyst might by placing the thesis on the couch.
Content removed due to copyright restrictions: Dickson, A. (2011). The jouissance of the lard(er): gender, desire and anxiety in the weight-loss industry. Culture and organization, 17(4), 313-328.
Keywords: Weight loss industry; Weight loss anxiety; Body image